La tutela del (coniuge) minore. Prospettive confessionali e prospettive civili (Stato, Chiese e pluralismo confessionale, 2014)
Contributo sottoposto a valutazioneSOMMARIO: 1. La progressiva residualità dell’ipotesi del matrimonio tra minori e i perduranti profili di interesse nella disciplina canonistica – 2. I diritti dei minori nel quadro delle relazioni di famiglia: un ambito più ampio da cui valutare il problema dell’osservanza dei precetti confessionali – 3. Due ipotesi dibattute alla prova dell’applicazione pratica: la tutela penale e i patti tra i coniugi nel procedimento di separazione.ABSTRACT The legal protection of specific subjective categories is a traditional issue for international scholars. This kind of argumentative strategy reached a particular relevance after the Second World War, but those normative instruments, considered in an International and Criminal Comparative Law’s point of view, seem probably out-of-date and especially not strictly relevant in the current national Private Law. Nowadays, in the European social system, many traditional cultures support the juridical relevance (erga omnes) of their own values and try to apply their constitutive rules to the statute of family and her members. Considering difficult conditions for a legislative response and limited possibilities for a new general discipline (even because these modifications, when eventually approved, created a certain discontent in their practical consequences), the most important solution should be to encourage more inclusive customs not based just on a radical idea of secularism and on a precarious pre-eminence of legislati